Diderot and Rousseau - Tunstall, K (Voltaire Foundation, 2017)
Marian Hobson’s work has made a seminal contribution to our understanding of the European Enlightenment, and of Diderot and Rousseau in particular. This book presents her most important articles in a single volume, translated into English for the first time. Hobson’s distinctive approach is to take a given text or problématique and position it within its intellectual, historical and polemical context. From close analysis of the underlying conceptual structures of literary texts, she offers a unique insight into the vibrant networks of people and ideas at work throughout Europe, and across disciplinary boundaries as diverse as literature and mathematics, medicine and music. In their translations of Hobson’s essays, Kate Tunstall and Caroline Warman present the primary sources in both the original eighteenth-century French and modern English, making the detail of these debates accessible to everyone, from the specialist to the student, whatever their academic discipline or interest. Kate E. Tunstall and Caroline Warman, Opening lines 1. Introduction. From Diderot to Rousseau via Rameau (2005) I. The Paradoxe sur le comédien 2. The Paradoxe sur le comédien is a paradox (1973) 3. Sensibility and spectacle: the medical context for the Paradoxe (1977) II. Le Neveu de Rameau 4. Pantomime, spasm and parataxis: Le Neveu de Rameau (1984) 5. Deictics and dialectics in Le Neveu de Rameau (1992) 6. Lists, parataxis and Le Neveu de Rameau (1995) III. Causality 7. Jacques le fataliste: the art of the probable (1985) 8. ‘Nexus effectivus’ and ‘nexus finalis’; causality in Rousseau’s Discours sur l’inégalité and the Essai sur l’origine des langues (1992) IV. Aesthetics 9. Philosophy and Rococo style (2002) 10. Diderot’s Lettre sur les sourds et muets: language and labyrinth (1976) 11. Kant, Rousseau and music (1980) V. Measurement 12. Architecture, analogy and proportion (1991) 13. How to take the measure of a character (2002) 14. Measuring statues, or, special neutrality (2004) Bibliography Index